Legal Analysis of Sibling Forbidden Relationships (Incest) - Kasmawati Andi; Bakhtiar (SHS Web of Conferences, 2022)
This research is qualitative, and the type of data source is secondary data, so the data collection technique used in this research is documentation. The analysis was carried out using content analysis data analysis. From this research, it was found that the law that regulates marriage Undang-Undang Nomor 1 Tahun 1974 tentang perkawinan sebagaiman telah diganti dengan Undang-Undang Nomor 16 Tahun 2019. In addition, marriage is also described in Kompilasi Hukum Islam Law article 39-point (1) letter a. In addition, civil law also regulates the prohibition of marriage which is explained in Article 30 of KUH. Thus, both in religious law and state law, inbreeding does not provide space at all. According to Islamic law, incest is strictly prohibited or forbidden in the religion as stated in the QS. An-Nisa: 22, 23 who should not and may not marry. By customary law, it is strictly forbidden to have incest or incest because it violates the norms and values that apply in society.